Pembelajaran Berbasis Nilai Berbantuan Multimedia dalam Meningkatkan Kompetensi Afektif Peserta Didik - Erna Retna Safitri (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2023)
This research is motivated by the understanding that the current reality shows that the approach that has been developing so far is more naturalistic-positivistic which refers to cognitive coherence. Whereas the cognitive aspect in the context of mastering the subject matter is not the ultimate goal of a learning process. Mastery of subject matter is not the end of the teaching process, but only as an intermediate goal for the formation of better behavior. This study aims to measure the affective competence of students in learning using a value-based approach with the aid of multimedia. Aspects that are measured are acceptance, response, value inculcation, organization of values ​​and characteristics. The research was conducted using a qualitative approach. Data collection is done by using a questionnaire technique. Respondents are students who teach General Biology courses. Learning is carried out using powerpoint-based interactive media while the implementation of value-based learning is inserted in learning activities and the content of teaching materials used. The results showed that the learning process in addition to increasing students' interest and motivation also made students show positive attitudes in terms of: 1) Receiving; 2) Response (responding); 3) Value investment (valuing); 4) Organization of values ​​(organization); 5) Characteristics of life (characterization).